The Analysis of Economic Growth and Human Development in Gorontalo Province - Fizza Anindhita; Muhammad Hasbi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2022)
Economic Development in Gorontalo Province has a high growth rate when compared to the national growth rate, but this is inversely proportional to the value of the Human Development Index (HDI) which is below the national value, even though HDI itself is one of the determining factors for the success of development in an area. Therefore, this study aims to see whether there is a relationship between economic growth and HDI in Gorontalo Province. This research method uses Granger causality analysis technique to see the reciprocal relationship between economic growth and HDI, as well as multiple linear regression analysis to see the effect of each HDI indicator on economic growth in Gorontalo Province. This study found that there is a mutually influencing relationship between economic growth and HDI. Regression analysis also explains that the education indicator of HDI has a positive and significant effect in increasing economic growth in Gorontalo Province, while the Health indicator has no significant effect. Through the results of this study, it is hoped that the Gorontalo Provincial government can determine the right policies to increase the HDI of the community by improving the quality of its community resources so that the economy will also increase.